EFEKTIVITAS KEBIJAKAN SUBSIDI PUPUK DI DESA SUKAASIH KECAMATAN SUKATANI KABUPATEN BEKASI - Adiraputra, Prasaktiyoga; Supyandi, Dika (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The government has spent a lot of money on fertilizer subsidies. However, from the results of various studies, there are still many problems in its implementation. Therefore, research to determine the effectiveness of fertilizer subsidies is interesting. This study aims to determine the effectiveness of the implementation of fertilizer subsidies. This research was conducted in Sukaasih Village, Sukatani District, Bekasi Regency. The research sample was determined by the multistage sampling method which resulted in a sample of 109 farmers. The data that has been obtained were analyzed using frequency distribution analysis. The results showed that the implementation of the fertilizer subsidy policy in Sukaasih Village was not effective. Therefore, the government needs to ensure the acceleration and mitigation of barriers to implementing farmer cards in the regions can be a solution so that fertilizer subsidies can be effective.